AKTIVITAS ANTIOKSIDAN DAN ANTIMIKROBA MINYAK JERUK PURUT (Citrus hystrix DC.) DAN KOMPONEN UTAMANYA - Warsito Warsito; Noorhamdani Noorhamdani; Sukardi Sukardi; Suratmo Suratmo (Journal of Environmental Engineering and Sustainable Technology, 2017)
Kaffir lime oil (C. hystrix DC.) is consist of a complex mixture of hydrocarbons terpenoids and terpenoids which contain oxygen are distributed in every part of the plant. In this research tested the antioxidant and antimicrobial activity, both against kaffir lime oil from twigs, leaves and rind including the main components citronellal. The antioxidant was evaluated by testing its ability to catch DPPH radical. Antimicrobial activity is measured by its ability to inhibit the growth of gram-negative bacteria, Escheria coli. Gas chromatography-mass spectrometry (GC-MS) is used to analyze chemical composition of kaffir lime oil. Value of IC50 of kaffir lime oil obtained was 6,43 (mL/mL); 6,83 (mL/mL); 9,48 (mL/mL) and 10,1 (mL/mL), consecutive to kaffir lime oil from rind, leaves, twig-leaf mixture and citronellal. Compared to the other kaffir lime oil and major components citronellal, kaffir lime oil from rind show the most vigorous activity in inhibiting growth of Escheria coli bacteria, by MIC values of 12,5 (mL/mL). GC-MS analysis showed that citronellal and citronellol as major component on kaffir lime oil from leaves and twig-leaf mixture, while the major component of kaffir lime oil from rind is b-pinene, limonene, citronellal dan terpinen-4-ol. Keywords: kaffir lime oil, citronellal, citronellol, antioxidant, antimicrobial